HHIP Overexpression Suppresses Human Gastric Cancer Progression and Metastasis by Reducing Its CpG Island Methylation - Song, Yu; Tu, Jianchen; Cheng, Yanan; Zhou, Fang; Liu, Peilin; Zhou, Shuangshuang; Gu, Yongjun; Sun, Yang (Frontiers in Oncology, 2020)
Human hedgehog-interacting protein (HHIP), a negative regulator of hedgehog (HH) signaling pathway, has been reported to be dysregulated in many types of cancer, including gastric cancer. However, the inhibitory role of HHIP as well as the underlying molecular mechanism of HHIP regulation in gastric cancer haven’t been fully elucidated yet. In this study, we demonstrated that HHIP overexpression significantly suppressed the proliferation and invasion of AGS cells evaluated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and transwell assays, respectively. Interestingly, methylation specific polymerase chain reaction (MS-PCR, MSP) showed that HHIP overexpression dramatically decreased its de novo promoter methylation levels in AGS cells. Furthermore, HHIP expression was higher in adjacent non-cancerous tissue compared to matched gastric cancer tissue. High HHIP level was negatively correlated with metastasis (p = 0.035) but not local recurrence (p = 0.58). Taken together, our study suggested that HHIP can modulate gastric cancer progression and metastasis via regulation of its de novo promoter methylation levels in a feedback manner. Lower HHIP levels is positively associated with gastric cancer metastasis, which not only indicates HHIP could be served as a protective marker for gastric cancer, but also suggests restoring HHIP expression might be a potential therapeutic strategy for clinical treatment.